Edukasi Lingkungan Keluarga dalam Meningkatkan Minat Literasi Anak dalam Sekolah di SDN Sempu Kecamatan Ngebel - Endang Prawati; Kadenun Kadenun (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to identify the role of parents in helping students at SD Sempu become more proficient in reading and writing, as well as to examine the forms of support provided by parents to enhance these skills. The research employed the Asset-Based Community Development (ABCD) method, which emphasizes the formulation of strategies to promote sustainable development by focusing on the strengths and resources within the community. The participants were parents of SD Sempu students, with a focus on the students’ reading and writing abilities. The findings reveal that most SDN Sempu students receive considerable attention, guidance, and support from their parents at home to improve their reading and writing skills. Many parents enroll their children in tutoring or private lessons, yet they also continue to provide direct assistance, which is crucial for elementary school children. However, some students still face challenges in reading and writing due to a lack of parental involvement. This study demonstrates that the role of parents greatly influences children’s success in reading and writing at SD Sempu.